2012
DOI: 10.1177/0022146512442676
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Processes, Self-Efficacy, and Adolescent Mental Health

Abstract: Self-efficacy beliefs are central to mental health. Because adolescents' neighborhoods shape opportunities for experiences of control, predictability, and safety, we propose that neighborhood conditions are associated with adolescents' self-efficacy and, in turn, their internalizing problems (i.e., depression/anxiety symptoms). We tested these hypotheses using three waves of data from the Project on Human Development in Chicago Neighborhoods (N = 2,345). Results indicate that adolescents living in violent neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 40 publications
5
67
0
1
Order By: Relevance
“…This finding is consistent with previous work identifying neighborhood safety and low socioeconomic status (SES) as risk factors for higher levels of psychopathology, including anxiety (Essex et al, 2006; Grant et al, 2003; Johnson et al, 1999; Simning, van Wijngaarden, & Conwell, 2012; Slopen, Fitzmaurice, Williams, & Gilman, 2012). These findings may be best explained by research finding that low self-efficacy indirectly links neighborhood safety and internalizing problems among youth (Dupéré, Leventhal, & Vitaro, 2012). Although excessive autonomy restriction by parents may facilitate decreased self-efficacy when faced with anxiety provoking situations, for children living in unsafe neighborhoods, the daily threat they experience and lack of control over their environment may be a more salient predictor of their anxiety than their parent’s behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous work identifying neighborhood safety and low socioeconomic status (SES) as risk factors for higher levels of psychopathology, including anxiety (Essex et al, 2006; Grant et al, 2003; Johnson et al, 1999; Simning, van Wijngaarden, & Conwell, 2012; Slopen, Fitzmaurice, Williams, & Gilman, 2012). These findings may be best explained by research finding that low self-efficacy indirectly links neighborhood safety and internalizing problems among youth (Dupéré, Leventhal, & Vitaro, 2012). Although excessive autonomy restriction by parents may facilitate decreased self-efficacy when faced with anxiety provoking situations, for children living in unsafe neighborhoods, the daily threat they experience and lack of control over their environment may be a more salient predictor of their anxiety than their parent’s behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Developmentally, young people are expected to craft occupational, educational, and relational aspirations for their lives and futures. In addition to the reality of constrained geographies of opportunity [31,32], fear of neighborhood violence may add to perceived stress and reduce future orientation among African Americans [33]. In unsafe neighborhoods, maintenance of survival may become a priority for the residents [34].…”
Section: Fear Of Neighborhood Violencementioning
confidence: 99%
“…A number of additional studies have demonstrated that youths with higher levels of street efficacy are less likely to be aggressive (Kirk & Hardy, 2014), to be anxious/depressed (Dupéré, Leventhal, & Vitaro, 2012), to be victimized (Gibson, Fagan, & Antle, 2014), to engage in violent behavior (Sharkey, 2006), and to witness community violence (Sharkey & Sampson, 2010). In short, street efficacy has been well-received as a theoretical and empirical contribution to the neighborhood effects literature (see Browning & Jackson, 2013).…”
Section: Street Efficacymentioning
confidence: 99%